Adjuvant activity of saponin and its fractions in foot and mouth disease vaccine - ΔΗΜΗΤΡΙΑΔΗΣ, I. A. (Journal of the Hellenic Veterinary Medical Society, 2019)
An assay was made to separate the adjuvant factor of saponin from the hemolytic using the chromatography method. A 40% saponin solution was passed through Sephadex G-25 column and the first fraction was passed again through Sephadex G-200 column. 2 out of 3 peaks obtained through Sephadex G-200 column were examined. These two peaks were compared with those obtained with Foodand -Mouth Disease vaccine containing a 40% saponin solution and concerning the capacity for hemolysis, necrosis and adjuvant effect of this vaccine. The 40% sapnonin solution gives hemolysis of sheep red cells (3% red cells washed and diluted in veronal buffer) when the quantity of saponin is at least 0,078 mg in the solution. The fraction A and Β obtained through G-25 column give hemolysis when the quantities of saponin are 0,156mg and 0,312mg respectively. The fraction II obtained through G-200 column gives hemolysis with 0,156mg while the fraction I does not give hemolysis even with a 10-fold quantity of saponin. The hemolysis was compared using a 3% suspension of sheep red cells and blood agar (1% agar with 3% sheep red cells). The hemolytic titre of saponin in blood agar Is 3 dilutions higher (with dilution logarithm 2) from the one on the suspension of red cells. This led us to think of using this method for detecting smaile quantities of saponin. The irritation and necrosis degree are different when saponin as a whole and its fraction are used. A 40% saponin solution containing 0,8mg of this substance gives 50% necrosis. To obtain the same degree of necrosis we need 3, 4mg and 1,13mg of saponin when fractions A and Β through G-25 are respectively used. When the fraction II through G-200 is used 3mg of saponin are needed, while the fraction I through the same column does not give any necrosis even used in 10-fold volume. Neutralizing antibodies titres in guinea pigs after vaccination and infection with the same Foot and-Mouth Disease virus subtype (A22) are fluctuating and do not correlate with the protection obtained in these animals. The PD! 0 in guinea pigs injected with a Food-and-Mouth disease vaccine (subtype A22) witout addition of saponin is 0,125 mg of vaccine. Adding in this vaccine a 40% saponin solution (that is 0,312mg of saponin per vaccine dose) the PD,0 in guinea pigs is 0,062. Using a lower saponin dilution (that is 0,625 mg per vaccine dose) the PDJ 0 in guinea pigs is 0,031ml of vaccine. The addition of fraction I and II though Sephadex G-200 does not have any influenc on the immunizing capacity of the vaccine